(untitled) (Mugda Medical College Journal, 2025)
Neutrophil-lymphocyte ratio (NLR) acts as an indicator of subclinical inflammation. A crosssectional study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka, Bangladesh, between January and December 2021, to assess the status of neutrophillymphocyte ratio in patients with type-2 diabetes mellitus (T2DM) and normoglycemic individuals in a Bangladeshi population. A total of 180 subjects were selected aged between 20 and 79 years. Among them, 60 relatively healthy subjects were selected as control group (group A), while 120 type 2 diabetic patients were included as study group (group B) for comparison. Participants’ age, gender, height, weight, waist circumference (WC) and blood pressure were recorded. Body mass index (BMI) was calculated. Then, blood samples were taken from the participants to see complete blood count (CBC), HbA1c, random blood glucose, serum creatinine and serum ALT were estimated. Receiver operating characteristic (ROC) curve was plotted to assess the NLR’s performance in diabetes mellitus prediction. The power of diabetes mellitus prediction was quantified by the area under the curve (AUC) with 95% confidence intervals. No differences were found between the groups in terms of participants’ age, gender, BMI, systolic and diastolic blood pressure (p>0.05). However, total WBC count, neutrohil count and neutrophil-lymphocyte ratio (NLR) was found higher and lower lymphocute count in type-2 diabetic patients compared to healthy controls (p<0.001). Measuring the predictive value of neutrophils-lymphocyte ratio in predicting diabetes mellitus, we found area under the curve (AUC) value of 0.819, SE 0.031 with 96.7% sensitivity and 70% specificity (p<0.001) through ROC curve analysis. Therefore, our data suggests that NLR can be used as prognostic tool during the follow up of the diabetic patients. Mugda Med Coll J. 2025; 8(1): 43-49